Risk of Heavy Metal Poisoning From Consuming Grasscutter Digesta in Ghana - Jude Tetteh Quarshie; Judah Kafui Cofie; Felix Selasi Dewornu; Osbourne Quaye; Anastasia Rosebud Aikins (SAGE Publishing, 2023)
Grasscutter (cane rat/ Thryonomys swinderianus ) digesta is used as a spice in Ghana. Research shows that heavy metals from the environment may accumulate in the internal organs of grasscutters, which raises concerns about the possible contamination of grasscutter digesta, too, with heavy metals. Although grasscutter meat in Ghana has been described as safe for consumption, information is lacking on the health risks associated with ingesting the digesta. This study, therefore, aimed to assess the knowledge and perceptions of a merchant and a consumer about the safety of ingesting grasscutter digesta and to evaluate potential health risks from exposure to heavy metals from the spice. A total of 12 digesta samples were analyzed to evaluate potential health risks from exposure to Cd, Fe, Hg, and Mn using a Varian AA240FS Atomic Absorption Spectrometer. The levels of Cd, Hg, and Mn were below the detection limit of 0.01 mg/kg digesta. Also, the estimated daily intake of Fe (0.02 mg/kg) was less than the maximum allowable dose recommended by the US EPA (0.7 mg/kg). The hazard indices of Fe for daily and weekly consumption were <1, suggesting that the consumers may be safe from iron poisoning. Because grasscutter digesta is a relatively expensive spice, it is unlikely to be consumed daily by the average Ghanaian. Moreover, if 10 g of digesta is consumed daily, it can be safely ingested about 971 times in a month. Domestication of grasscutters may be a useful approach to monitor their diet and consequently the quality of their digesta.